Intuitionistic Fuzzy Sets in Career Determination (Global Journal of Science Frontier Research, 2014)
Intuitionistic fuzzy set has proven interesting and useful in providing a flexible framework or model to elaborate uncertainty and vagueness involved in decision making. In this paper, we proposed the application of intuitionistic fuzzy sets (IFS) in career determination. Solution is obtained by looking for the smallest distance between each student and each career.
Keywords: fuzzy sets; intuitionistic fuzzy sets; career choice; career determination